Nephrologist Follow-Up versus Usual Care after an Acute Kidney Injury Hospitalization (FUSION): A Randomized Controlled Trial. Issue 7 (July 2021) - Silver, Samuel A.; Adhikari, Neill K.; Bell, Chaim M.; Chan, Christopher T.; Harel, Ziv; Kitchlu, Abhijat; Meraz-Muñoz, Alejandro; Norman, Patrick A.; Perez, Adic; Zahirieh, Alireza; Wald, Ron
Visual Abstract: Abstract : Background and objectives: Survivors of AKI are at higher risk of CKD and death, but few patients see a nephrologist after hospital discharge. Our objectives during this 2-year vanguard phase trial were to determine the feasibility of randomizing survivors of AKI to early follow-up with a nephrologist or usual care, and to collect data on care processes and outcomes. Design, setting, participants, & measurements: We performed a randomized controlled trial in patients hospitalized with Kidney Disease Improving Global Outcomes (KDIGO) stage 2–3 AKI at four hospitals in Toronto, Canada. We randomized patients to early nephrologist follow-up (standardized basket of care that emphasized BP control, cardiovascular risk reduction, and medication safety) or usual care from July 2015 to June 2017. Feasibility outcomes included the proportion of eligible patients enrolled, seen by a nephrologist, and followed to 1 year. The primary clinical outcome was a major adverse kidney event at 1 year, defined as death, maintenance dialysis, or incident/progressive CKD. Results: We screened 3687 participants from July 2015 to June 2017, of whom 269 were eligible. We randomized 71 (26%) patients (34 to nephrology follow-up and 37 to usual care). The primary reason stated for declining enrollment included hospitalization-related fatigue ( n =65), reluctance to add more doctors to the health care team ( n =59), and long travel times ( n =40). Nephrologist visits occurred in 24 of 34 (71%) intervention participants, compared with three of 37 (8%) participants randomized to usual care. The primary clinical outcome occurred in 15 of 34 (44%) patients in the nephrologist follow-up arm, and 16 of 37 (43%) patients in the usual care arm (relative risk, 1.02; 95% confidence interval, 0.60 to 1.73). Conclusions: Major adverse kidney events are common in AKI survivors, but we found the in-person model of follow-up posed a variety of barriers that was not acceptable to many patients. Clinical Trial registry name and registration number: Nephrologist Follow-up versus Usual Care after an Acute Kidney Injury Hospitalization (FUSION), NCT02483039 CJASN 16: 1005–1014, 2021. doi: https://doi.org/10.2215/CJN.17331120